UPAYA MENINGKATAN HASIL BELAJAR MATEMATIKA SISWA KELAS VI SD MUHAMMADIYAH BANTUL MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE THE POWER OF TWO - Saiful Mujab (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2023)
This study aims to determine the use of The Power of Two model in mathematics learning can improve student learning outcomes in grade VI SD Muhammadiyah Bantul. This research is a qualitative descriptive classroom action research (PTK) which is strengthened by a quantitative approach, while the object of research is to improve learning outcomes in mathematics learning using The Power of Two model. This research was conducted in two cycles and went through four stages which include: (1) Planning, (2) Implementation, (3) Observation and (4) Reflection. Data is obtained through observation, interviews, tests, doing questions and documentation. Data analysis was carried out using the results of cycle I and cycle II learning tests, the approach in cycle I showed that all learning activities were not well enough to be carried out by students even though they experienced an increase in cycle I compared to pre-cycle and still at less predicate, because the average percentage was still below 75%. Cycle II has shown satisfactory results both from student learning activities have been in the predicate of sufficient, good and very good, while student learning outcomes have reached an average of 86% with a classical percentage of 90%, meaning that corrective actions for the learning process have been sufficient and reached the criteria.